Influência de dietas com diferentes concentrações lipídicas com elevada relação ômega9/ômega 6 e baixa relação ômega 6/ômega 3 sobre o fígado de ratos na vigência da carcinogênese cólica induzida por azoximetano - Veras, Lara Burlamaqui (2015)
Colorectal and hepatic cancer have an increasing incidence and are influenced by genetic and environmental factors, one of the most important is diet. Azoxymethane (AOM) is used to induce colonic carcinogenesis in experimental models. In the liver, AOM cause cellular changes similar to those seen in chronic liver injury models. Fatty acids -3, -6 and -9 are believed to be involved in the pathogenesis and prevention of carcinogenesis. The objective was to evaluate the hepatic and systemic effects in rats fed hyperlipidic, normolipidic and hypolipidic diets with low -6:-3 ratio and high -9:-6 ratio in the presence of colonic carcinogenesis AOM-induced. Sixty 3-week-old male Wistar rats weighing 50g were assigned to 5 groups of 12 each: GI=Standard diet without AOM; GII=Standard diet and AOM; GIII=Hyperlipidic diet and AOM; GIV=Normolipidic diet and AOM; GV=Hypolipidic diet and AOM. Weight and ingestion were registered 4 times/week until the 36th week. Colons and livers were analyzed for macroscopic and microscopic changes. The levels of total and fractionated cholesterol, triglycerides, glycemia, ALT, AST, glutathione, TBARS were determined in plasma. Ingestion was greater in GI and GII than in GIII, GIV and GV. Body mass was greater in GI and GII than in GIII, GIV and GV. The ratio between liver’s weight and animal’s final weight was higher in GV than all the other groups. In GV, the incidence of colonic tumors and pre-neoplastic and benign neoplastic liver lesions were reduced. Glutathione was higher and TBARS was lower in GV. In conclusion, hyperlipidic, normolipidic and hypolipidic diets with low -6:-3 ratio and high -9:-6 ratio reduce ingestion, body mass, appearance of colonic tumors and pre-neoplastic and benign neoplastic liver lesions, lipid peroxidation and increase the antioxidant capacity. Hypolipidic diet